Decrease of Building’s Humidity with Epiphyte and Xerophyte - Wahjutami, Erlina Laksmiani; Antariksa, Antariksa; Nugroho, Agung Murti; Leksnono, Amin Setyo (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2015)
This article is part of the research phase in Environmental Sciences Doctoral study program that is interdisciplinary research, ongoing. Architecture disciplines collaborate with the disciplines of biology to solve the problem of the microclimate in the built. Paradigm used as benchmarks is bioclimatic architecture in which there is a relationship between elements of the building, climate, and living organisms. Living organisms - in this case the plant - used as a tool to solve the problem of the microclimate in buildings. Plant is one of the living organisms that grow and thrive in their respective habitats and the climate of each character. Several studies have shown that plants are able to lower both ambient temperature and the temperature inside the building. In this study, the problem is the existence of a higher humidity levels in small type of dwelling (STD) that has been totally renovated. Meanwhile Epiphytic and Xerophyte are plants that live by absorbing surrounding moisture. In the next stage of research, it is expected that the capability of Epiphyte and Xerophyte’s plants to reduce the building’s humidity proven. From the interpretation Q.S. 23: 17, implied that: Allah has bring down the water to the earth to grow a variety of plants [1]. The diversity of these plants would be useful for people who have sense. Building as the built environment will become sustainable environment when the human capable of utilizing plants as part of it.